Pathways to accountability in rural Guatemala: A qualitative comparative analysis of citizen-led initiatives for the right to health of indigenous populations. (January 2019) - Hernández, Alison; Ruano, Ana Lorena; Hurtig, Anna-Karin; Goicolea, Isabel; San Sebastián, Miguel; Flores, Walter
Highlights: Analyzes citizen actions, contextual conditions and outcomes in 29 cases of initiatives for health system accountability in Guatemala. Highlights pathways involving network building, monitoring and engagement with different authorities and how they lead to responsive action. Iterative cycles of collective action are critical for activating the power of marginalized citizens to demand accountability from authorities. Initiatives employ constructive and adversarial engagement strategies to achieve solutions to the health system failures they face. Abstract: Strengthening citizen-led accountability initiatives is a critical rights-based strategy for improving health services for indigenous and other marginalized populations. As these initiatives have gained prominence in health and other sectors, there is great interest in how they operate and what makes them effective. Scholarly focus is shifting from measuring the efficacy of their tools and tactics to deepening understanding of the context-sensitive pathways through which change occurs. This paper examines how citizen-led initiatives' actions to strengthen grassroots networks, monitor health services and engage with authorities interact with local sociopolitical conditions and contribute to accountability achievements for indigenous populations in rural Guatemala. We used qualitative comparative analysis to first systematize and score structured qualitative monitoring data gathered in 29 municipal-level initiatives, and then analyze patterns in the presence of different forms of citizen action, contextual conditions and accountability outcomes across cases. Our study identifies pathways of collective action through which citizen-led initiatives bolster their power to engage and negotiate with authorities and bring about solutions to some of the health system deficiencies that they face. While constructive engagement is widely advocated as the most effective approach to interaction with authorities, our study indicates that success depends on wider processes of community mobilization. To overcome the power asymmetries that marginalized groups face when engaging with authorities, iterative processes of network building and participatory monitoring as well as persistence in their demands are critical. These processes further provide an enabling environment for moving beyond the local and projecting indigenous voices to engage with authorities at higher governance levels. Initiatives also applied adversarial legal action as an alternative engagement strategy that contributed to bolster citizen power. Our findings indicate the potential of collective power generated by the actions of citizen-led initiatives to enable marginalized populations to hold authorities accountable for health system failures.